The Expectations Hypothesis, the Yield Curve, and Monetary Policy: Comment - Cox, Jack W.; Deming, Frederick W. (Quarterly Journal of Economics, 1966)
Journal Article The Expectations Hypothesis, the Yield Curve, and Monetary Policy: Comment Get access Jack W. Cox, Jack W. Cox Federal Reserve Bank of New York Search for other works by this author on: Oxford Academic Google Scholar Frederick W. Deming Frederick W. Deming Federal Reserve Bank of New York Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 80, Issue 2, May 1966, Pages 333–335, https://doi.org/10.2307/1880697 Published: 01 May 1966